2012
DOI: 10.1089/ast.2011.0812
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Genomic, Stable Isotopic, and Lipid Analyses of a Modern Freshwater Microbialite from Cuatro Ciénegas, Mexico

Abstract: Microbialites are biologically mediated carbonate deposits found in diverse environments worldwide. To explore the organisms and processes involved in microbialite formation, this study integrated genomic, lipid, and both organic and inorganic stable isotopic analyses to examine five discrete depth horizons spanning the surface 25 mm of a modern freshwater microbialite from Cuatro Ciénegas, Mexico. Distinct bacterial communities and geochemical signatures were observed in each microbialite layer. Photoautotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 79 publications
(104 reference statements)
7
33
0
Order By: Relevance
“…Similar trends have also been reported in the freshwater microbialites of Cuatros Ciénegas, Mexico (Nitti et al 2012). Results from these studies, which used a combined genomic, lipid and stable isotope analyses, also showed distinct spatial differences within the lithifying communities although no lithified layers were present (Nitti et al 2012) reinforcing the idea that the microbial communities can form discrete metabolic zones within unlaminated microbialite forming communities.…”
Section: Gradients Of Metabolic Potential Occur Within the Depth Profsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar trends have also been reported in the freshwater microbialites of Cuatros Ciénegas, Mexico (Nitti et al 2012). Results from these studies, which used a combined genomic, lipid and stable isotope analyses, also showed distinct spatial differences within the lithifying communities although no lithified layers were present (Nitti et al 2012) reinforcing the idea that the microbial communities can form discrete metabolic zones within unlaminated microbialite forming communities.…”
Section: Gradients Of Metabolic Potential Occur Within the Depth Profsupporting
confidence: 79%
“…Similar trends have also been reported in the freshwater microbialites of Cuatros Ciénegas, Mexico (Nitti et al 2012). Results from these studies, which used a combined genomic, lipid and stable isotope analyses, also showed distinct spatial differences within the lithifying communities although no lithified layers were present (Nitti et al 2012) reinforcing the idea that the microbial communities can form discrete metabolic zones within unlaminated microbialite forming communities. Although the metagenomic survey correlated many of the specific pathways associated with the use of these different substrates, future work is required to delineate the specific expression of these molecular pathways to assess how the various metabolic activities are coordinated and regulated throughout the vertical profile of these lithifying microbial communities.…”
Section: Gradients Of Metabolic Potential Occur Within the Depth Profsupporting
confidence: 79%
See 1 more Smart Citation
“…Boon et al, 1983;Boudou et al, 1986a,b;Grimalt et al, 1992;Bühring et al, 2009;Sherf and Rullkötter, 2009;Nitti et al, 2012;Pagès et al, 2014;Blumenberg et al, 2015). Lipid biomarkers were analysed for 5 out of the 7 sampled mat layers (Fig.…”
Section: Biomarker Characterization and Inferred Sourcesmentioning
confidence: 99%
“…Shearman and Skipwith (1965) suggested that the mucilaginous jackets which surround most shallow-water carbonate grains could be the source of much of the kerogen in carbonate rocks. Although Nitti et al (2012) explored the vertical changes in the microbial community in lacustrine stromatolites, only a few studies have explored the vertical variation in bacterial and archaeal communities in zones of carbonate and evaporite precipitation (Kenig et al, 1990;Kendall et al, 2002). Kenig et al (1990), together with Baltzer et al (1994), analysed the OM in shallow-water lagoonal and intertidal sediments in Abu Dhabi.…”
Section: Introductionmentioning
confidence: 99%